1997
DOI: 10.1182/blood.v89.10.3769
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Expression of Antiapoptotic BCL-2 Oncoprotein in Newly Diagnosed Childhood Acute Lymphoblastic Leukemia: A Children's Cancer Group Study

Abstract: We found a marked variation in BCL-2 oncoprotein expression levels of primary leukemic cells from 338 children with newly diagnosed acute lymphoblastic leukemia (ALL). None of the high-risk features predictive of poor treatment outcome in childhood ALL, such as older age, high white blood cell (WBC) count, organomegaly, T-lineage immunophenotype, ability of leukemic cells to cause overt leukemia in severe combined immunodeficient (SCID) mice, presence of MLL-AF4, and BCR-ABL fusion transcripts were associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 48 publications
2
16
0
3
Order By: Relevance
“…Levels of bcl-2 expression among our precursor B-ALL cases, although higher than haematogones, were quite variable, similar to what others have reported for both paediatric and adult precursor B-ALL (Campos et al, 1996;Coustan-Smith et al, 1996;Uckun et al, 1997). As mentioned previously, levels of bcl-2 in precursor B-ALL do not appear to correlate with Bcl-2 analysis of a post-treatment B-ALL marrow specimen.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Levels of bcl-2 expression among our precursor B-ALL cases, although higher than haematogones, were quite variable, similar to what others have reported for both paediatric and adult precursor B-ALL (Campos et al, 1996;Coustan-Smith et al, 1996;Uckun et al, 1997). As mentioned previously, levels of bcl-2 in precursor B-ALL do not appear to correlate with Bcl-2 analysis of a post-treatment B-ALL marrow specimen.…”
Section: Discussionsupporting
confidence: 87%
“…(B) However, mean bcl-2 levels are higher than those in the more mature B-cell and T-cell populations that are also present, consistent with recurrent B-ALL. clinical responses to treatments or markers of prognosis (Campos et al, 1996;Coustan-Smith et al, 1996;Uckun et al, 1997;Hogarth & Hall, 1999). The variation in levels of bcl-2 expression observed in our B-ALL cases also did not appear to correlate with any phenotypic features of our cases.…”
Section: Discussionmentioning
confidence: 44%
“…Targeting Apoptosis in Leukaemias with t(4;11) ÂȘ 2008 The Authors Journal Compilation ÂȘ 2008 Blackwell Publishing Ltd, British Journal of Haematology, 141, 827-839 described before (Maung et al, 1994;Coustan-Smith et al, 1996;Uckun et al, 1997). Similarly, variable and sometimes substantial BCL2 mRNA expression levels also were detected in the other leukaemia subtypes studied here; however, these results should be interpreted with caution because only a small number of cases were examined.…”
Section: Discussionmentioning
confidence: 49%
“…In a previous study, we demonstrated that in childhood acute lymphoblastic leukaemia (ALL) the interpatient levels of Bcl-2 and Bax, as well as the Bax to Bcl-2 ratio, are highly variable. Lower Bcl-2 correlated with factors commonly associated with unfavourable prognosis i.e., WBC, T-lineage, (Salomons et al, 1997;Uckun et al, 1997) chromosomal translocations and poor outcome (Coustan-Smith et al, 1996). By contrast, Bax and the Bax:Bcl-2 did not correlate with clinical features at presentation (Salomons et al, 1997), but the values of Bax:Bcl-2 found in untreated blasts spans the range of values that in in vitro models corresponded to increased sensitivity to glucocorticoid-induced apoptosis (Brady et al, 1996;Salomons et al, 1997).…”
mentioning
confidence: 85%